Improving The Quality of Education Through The Principal's Strategy to Develop Teacher Competence - Ahmad Syukkur; Fauzan Fauzan (Nazhruna: Jurnal Pendidikan Islam, 2021)
Principal's strategy is the art and knowledge gained by a principal in formulating, implementing, evaluating cross-functional decisions that facilitate the organization in achieving goals. Teachers are the key to the success of an educational institution. Good and bad behavior or teaching procedures for teachers will greatly affect the image of educational institutions. This study aims to examine and discuss in-depth the principal's strategy in developing teacher competence at MA Tarbiyatul Islam Gending Probolinggo. This study uses a descriptive qualitative approach. Data collection techniques with interviews, observations, and documentation. The results of the study indicate that: (1) The model that can be used to improve the competence of teachers in carrying out their duties is through In-service education or In-service training programs. (2) The strategic steps of the principal's leadership in developing teacher competence to improve the quality of education are the first formal strategy, namely the teacher is assigned by the institution to attend education and training, the second non-formal strategy, namely the teacher on his own desire and effort to train and develop himself related to work or position.